Early assessment with magnetic resonance imaging for prediction of pathologic response to neoadjuvant chemotherapy in triple-negative breast cancer: Results from the phase III BrighTNess trial. Issue 2 (February 2020) - Golshan, Mehra; Wong, Stephanie M.; Loibl, Sibylle; Huober, Jens Bodo; O'Shaughnessy, Joyce; Rugo, Hope S.; Wolmark, Norman; Ansell, Peter; Maag, David; Sullivan, Danielle M.; Metzger-Filho, Otto; Von Minckwitz, Gunter; et al.
Abstract: Introduction: The ability of breast magnetic resonance imaging (MRI) to predict pathologic complete response (pCR) to neoadjuvant systemic therapy (NST) varies across biological subtypes. We sought to determine how well breast MRI findings following initial treatment on the phase III BrighTNess trial correlated with pCR in patients with triple negative breast cancer (TNBC). Methods: Baseline and mid-treatment imaging and pathologic response data were available in 519 patients with stage II-III TNBC who underwent NST as per protocol. MRI complete response (mCR) was defined as disappearance of all target lesion(s) and MRI partial response (mPR) as a ≥50% reduction in the largest tumor diameter. Results: Overall, mCR was demonstrated in 116 patients (22%), whereas 166 (32%) had mPR and 237 (46%) had stable/progressive disease (SD/PD). The positive predictive value (PPV), negative predictive value, and overall accuracy of the mid-treatment MRI for pCR were 78%, 56%, and 61%, respectively; accuracy did not differ significantly between gBRCA mutation carriers and non-carriers (52% vs. 63%, p = 0.10). When compared to patients with SD/PD, those with mPR or mCR were 3.35-fold (95% CI 2.07–5.41) more likely to have pCR at surgery. MRI response during NST was significantly associated with eligibility for breast-conserving surgery following completion of treatment (93.1% for mCR vs. 81.6% for SD/PD, p < 0.001). Conclusions: Complete response on mid-treatment MRI in the BrighTNess trial had a PPV of 78% for demonstration of pCR after completion of NST in TNBC. However, a substantial proportion of patients with mPR or SD/PD also achieved a pCR. Clinical trial registration: NCT02032277 .